THE EFFECT OF TRANEXAMIC ACID INJECTION ON HEMOGLOBIN LEVEL, ALBUMIN LEVEL, AND PAIN ON PATIENT RECEIVING TOTAL KNEE REPLACEMENT - Dwikora Novembri Utomo; Teddy Heri Wardhana; Ahmad Hannan Amrullah; Hamzah Hamzah (Journal Orthopaedi and Traumatology Surabaya)
Background: The high number of knee osteoarthritis cases could lead arthroplasty more frequent. Total Knee Replacement (TKR) surgery procedure is at risk of massive bleeding. Bleeding can affect albumin levels and the onset of intra-compartment pressure on the nerves. The use of tranexamic acid could be done to reduce bleeding.